Service Quality and Customer Satisfaction: An Empirical Investigation of Telecom Users in Chitwan - Timilsina, Nikita; Wagle, Sudip (BMC Journal of Scientific Research, 2025)
This study investigate the relationship between customer satisfaction and service quality in regard to the telecom sector in Nepal in terms of reliability, price fairness, signal strength, responsiveness and coverage with a particular focus to the Chitwan district. A standardized questionnaire was used to collect data among 384 Nepal Telecom (NTC) and Ncell subscribers. The analysis was done by using SPSS and both descriptive and inferential statistics were employed, Cronbach alpha was applied to verify the reliability of the measurement scales. Four service quality measures were significantly positively correlated with customer satisfaction (p < 0.01). Regression findings showed that the pricing fairness did not significantly affect the customer satisfaction in the Nepalese telecom market, but reliability, strength of signal, responsiveness, and coverage were most influential. In order to enhance customer satisfaction telecom providers must consider improving network reliability and coverage, customer responsiveness through customer service, and fair pricing policies. This study contributes localized information to managerial decision making in the emerging markets and bridges an empirical research gap on the association between service quality and customer satisfaction in Nepal telecom industry in chitwan.